2017
DOI: 10.1155/2017/3039713
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of Thromboembolism and Endovascular Management

Abstract: Venous thromboembolism (VTE), a disease that includes deep venous thrombosis (DVT) and pulmonary embolism (PE), is associated with high mortality, morbidity, and costs. It can result in long-term complications that include postthrombotic syndrome (PTS) adding to its morbidity. VTE affects 1/1000 patients, costs $13.5 billion annually to treat, and claims 100,000 lives annually in the US. The current standard of care for VTE is anticoagulation, though thrombolysis may be performed in patients with PE and threat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 83 publications
0
34
1
3
Order By: Relevance
“…In a mouse models of ARDS, infection with the influenza virus increases platelet aggregation, pulmonary microvascular thrombosis, endothelial damage and the hyper-inflammatory cytokine responses [26,27,28]. Dysregulation of these same physiologic responses have been associated with pulmonary embolism (PE) [29], and prior studies have described PE in the setting of influenza infection [2,3].…”
Section: Discussionmentioning
confidence: 99%
“…In a mouse models of ARDS, infection with the influenza virus increases platelet aggregation, pulmonary microvascular thrombosis, endothelial damage and the hyper-inflammatory cytokine responses [26,27,28]. Dysregulation of these same physiologic responses have been associated with pulmonary embolism (PE) [29], and prior studies have described PE in the setting of influenza infection [2,3].…”
Section: Discussionmentioning
confidence: 99%
“…[49][50][51][52] Additionally, studies have demonstrated that QI initiatives paired with improved communication between care team members and education emphasizing the importance of VTE prophylaxis can lead to higher rates of appropriate prophylaxis. [53][54][55] Our own institution's use of the DMAIC framework led us to implement many of the previously supported counter- Through the recognition of these patient variables the system can further eliminate VTE prophylaxis that is contraindicated or simply not indicated, that is, enoxaparin in the context of decreased renal function or low dose (5000 unit) heparin for patients with BMI > 40 kg/m 2 .…”
Section: Eras and Vte-prophylaxismentioning
confidence: 99%
“…In 2007 this pathology was found to be responsible for about 12% of deaths in Europe (Amaral, & Tavares, 2013) and direct healthcare costs related to VTE in the European Union per year range from 1.5 to 13.2 (Behravesh, Hoang, Nanda, Wallace, Sheth, Deipolyi, & Oklu, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In the long term complications of VTE such as post-thrombotic syndrome and chronic pulmonary hypertension may arise (Behravesh, Hoang, Nanda, Wallace, Sheth, Deipolyi, & Oklu, 2017) which may increase hospital admission days and future hospital admissions. Given the importance of this issue, VTE prophylaxis is one of the most costeffective measures of clinical practice and is a priority strategy to improve the safety of hospitalized patients (Amaral & Tavares, 2013).…”
Section: Introductionmentioning
confidence: 99%